Forcing vine regrowth under different irrigation strategies: effect on polyphenolic composition and chromatic characteristics of cv. Tempranillo wines grown in a semiarid climate - Lavado Rodas, Nieves; Uriarte Hernández, David; Moreno Cardona, Daniel; Mancha Ramírez, Luis A.; Prieto Losada, María Henar; Valdés Sánchez, María Esperanza (Frontiers in Plant Science, 2023)
One of the effect of climate change in warm areas is the asynchrony between the dates of the technological and the phenolic maturity of grapes. This is important because the quality and colour stability of red wines are directly related to the content and distribution of phenolic compounds. A novel alternative that has been proposed to delay grape ripening and make it coincide with a seasonal period more favourable for the formation of phenolic compounds is crop forcing. This consists of severe green pruning after flowering, when the buds of the following year have already differentiated. In this way, the buds formed during the same season are forced to sprout, initiating a new delayed cycle. The aim of the present work is to study the effect on the phenolic composition and colour of wines elaborated from vines fully irrigated (C), grown using conventional non-forcing (NF) and forcing (F) techniques (C-NF and C-F), and wines from vines subjected to regulated irrigation (RI), grown using NF and F techniques (RI-NF and RI-F). The trial was carried out in an experimental vineyard of the Tempranillo variety located in a semi-arid area (Badajoz, Spain) in the 2017-2019 seasons. The wines (four by treatment) were elaborated and stabilised according to the classic methodologies for red wine. All wines had the same alcohol content and malolactic fermentation was not carried out in any of them. Anthocyanin profiles were analysed by HPLC, and total polyphenolic content, anthocyanin content, catechin content, the contribution to colour due to co-pigmented anthocyanins, and various chromatic parameters were also determined. Although a significant effect of year was found for almost all the parameters analysed, a general increasing trend in F wines was found for most of them. The anthocyanin profile of F wines was found to differ from that of C wines, especially in delphinidin, cyanidin, petunidin and peonidin content. These results indicate that by using the forcing technique it was possible to increase the polyphenolic content by ensuring that the synthesis and accumulation of these substances occurred at more suitable temperatures.